Removing the Australian tax exemption on healthy food adds food stress to families vulnerable to poor nutrition. - Landrigan, T.; Kerr, Deborah; Dhaliwal, S.; Savage, V.; Pollard, C. (Wiley-Blackwell Publishing Asia, 2017)
OBJECTIVE: To assess the impact of changing the Australian Goods and Services Tax (GST) on household food stress, which occurs when >25% of disposable income needs to be spent on food. METHODS: Weekly healthy meal plan costs for average-income (AI), low-income (LI) and welfare-dependent (WDI) families were calculated using the 2013 Western Australian (WA) Food Access and Costs Survey. Four GST scenarios were compared: 1) status quo; 2) increasing GST to 15%; 3) expanding base to include exempt foods at 10% GST; and 4) expanding base to include exempt foods and increasing the tax to 15%. RESULTS: Single-parent families risk food stress regardless of their income or the GST scenario (requiring 24-42% of disposable income). The probability of food stress in Scenario 1 is 100% for WDI two-parent families and 36% for LI earners. In Scenarios 3 and 4, food stress probability is 60-72% for two-parent LI families and AI single-parent families, increasing to 88-94% if residing in very remote areas. CONCLUSION: There is food stress risk among single-parent, LI and WDI families, particularly those residing in very remote areas. Implications for public health: Expanding GST places an additional burden on people who are already vulnerable to poor nutrition and chronic disease due to their socioeconomic circumstances.